Radical feminist representation, social cognition, and film communication on reducing sexual harassment - Razali, Geofakta; Oktaviana, Devita (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
Film is a work of art that has become a phenomenon in modern life that always produce a content that relate with social and human cognition affect in modern lifestyle, one of them is a sexual and a fight of woman. Sexual violence is an act of degrading, insulting, harassing or attacking a person's body, and reproductive function, due to the inequality of power and gender relations, which results in psychic and physical suffering which includes interfering with a person's reproductive health. In this study, the author's goal is to describe and analyze forms of sexual harassment through scenes in the Photocopier film in order to reduce the existence of sexual harassment, to describe and analyze the views in the film Photocopier so that film audiences can be more concerned about sexual harassment. The theory used in this study is Teun A. van Dijk's Critical Discourse Analysis with the methods carried out in this study are qualitative with data collection techniques used, namely observation, documentation and literature studies. In this study, it shows that sexual harassment is the factor most feared by victims, the figure of Farah, Tariq, and other victims suffering in silent, refusing to giving  up and find out the perpetrator of the sexual abuse experienced by them for fear that in the future negative things will happen consequently, in contrast to Suryani a victim who had the courage to try uncovering the events that she has experienced, Suryani relentlessly tried to find evidence of who is the mastermind behind the sexual harassment. The process of social cognition on the Suryani as an actress and the main character, can be found through critical discourse analysis methode by indicating the actress who manages and stores any information about sexual harassment committed, collects evidence, and fights for the right to justice. Keywords:  Film Communication, Photocopier, Sexual Harassment, Critical Discourse Analysis, Feminist